User satisfaction toward baby room design and facilities in selected shopping centers in Klang Valley, Malaysia - Yeong, Yin Mei (2014)
The World Health Organization (WHO) is known to advocate breastfeeding. Nevertheless, Borneo Post Online reported, the breastfeeding rate in Malaysia has been worrying low and such declining trend seems to be apparent in other Asian countries as well. One of the factors that could contribute to the unwillingness of Malaysian mothers to breastfeed is the lack of baby care and parenting facilities, which are installed in baby rooms in public places.The purpose of this research is to examine user satisfaction with the design and facilities of baby rooms in shopping centers in Klang Valley, to identify factors that affect user satisfaction with the design and facilities provided as well as develop recommendation on how the design and facilities of baby rooms can be enhanced. To investigate, a series of questionnaire surveys was conducted in the selected shopping centers in Klang Valley, Malaysia. The data analyses were conducted in the form of descriptive analyses which involve T-Test and Annova that were obtained by utilizing the statistical analysis program, SPSS 21. The findings revealed that the respondents were satisfied a little for all components in the baby room and particularly scored the lowest mean for security system in the baby room. Subsequently, some new and effective suggestions particularly for the provision of security and space planning for a baby room are proposed. This suggest that there is an imperative for shopping centers to improve and renew the design approach of a baby rooms, especially for security aspect to ensure that it is comfortable, beautiful and functional for space users. It is anticipated that this new will encourage space users to occupy baby room and mothers to breastfeed their baby which in turn would lead to improve the breastfeeding rate in Malaysia.